Development of a strategy of physician-patient relationship for improving care for patients with disorders of sex development: a qualitative study - Telles-Silveira, Mariana; Knobloch, Felicia; Kater, Claudio Elias (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Care for patients with disorders of sex development (DSD) should be provided in integrated-care centers by a multidisciplinary team. Implementation of this project within the teaching clinic routine presents several challenges: 1) difficulties in relationships between the medical team and patients and their families; 2) age, ethnic and cultural differences; 3) DSD-related prejudice; and 4) physicians’ anxiety. We report on a psychologist’s work strategy that focused on creating arrangements that could contribute towards development of the relationship between the medical team and patients and their families, as a way of preparing the clinical staff to manage treatment of adult DSD patients. DESIGN AND SETTING: Prospective qualitative study. METHODS: Between February 2010 and April 2015, we conducted a qualitative study in the Adrenal Outpatient Clinic of Escola Paulista de Medicina (São Paulo, Brazil), based on interviews, team discussions and group dynamics with resident physicians, postgraduate students and attending physicians. RESULTS: Implementation of the project allowed residents to build a story of differentiated care for their patients, thus facilitating dialog between them and making it possible to address taboo topics. Sequential care provided by the same resident led patients to feel that their doctor cared for them, with individuality, continuity and a sense of interest in their story. CONCLUSION: Presence of a psychologist in the outpatient routine enabled inclusion of subjective factors in the routine of medical consultations, thus broadening the notion of healthcare for patients with DSD, facilitating bonds and providing support for difficulties faced.